(untitled) (Annals of Medical Research, 2021)
Aim: This study was planned to determine the effect of Fraxin against damage of lung and testis tissues induced by testicular torsion detorsion in the experimental animals. Material and Methods: For this aim, in this study, experimental animals were weighed and randomize grouped. Groups were designed as sham, testicular torsion/detorsion (TTD), 10 mg/kg Fraxin + TTD (10 mg/kg for 15 days i.p.+2 h torsion;2 h detorsion) and 50 mg/kg Fraxin + TTD (50 mg/kg for 15 days i.p.+2 h torsion;2 h detorsion) groups. After the detorsion period was completed, all subjects were sacrificed by high-dose anaesthesia. At the end of the experiment, testis and lung tissues of rats were taken rapidly for biochemical analyzes. Results: When evaluating current biochemical data, Total oxidant status and malondialdehyde level were significantly elevated, and total antioxidant status and superoxide dismutase activity decreased significantly in the TTD group compared to the sham group (p0.001). On the contrary, in the groups applied the doses of 10 and 50 mg/kg of fraxin, the level of oxidant were decreased and the level of antioxidant was increased (p0.001). Conclusion: These results demonstrate that the applications of fraxin at 10 and 50 mg/kg doses show the protective effect on lung and testicular tissue, demonstrating a positive effect on experimental TTD injury in rats.